Malaysia’s blue carbon overview - Razzaq Khan, Waseem; Demies, Malcom; Memon, Abdul Razaque; Koh, Jane (Springer, 2024)
Climate change is one of the greatest challenges in the world and attracted many countries to mitigate greenhouse gas emissions through several mechanisms. Blue carbon has captured great interest recently. Malaysia has untapped blue carbon especially mangrove forests. The online review suggested that there are still a limited number of scientific studies on the overall aspect of blue carbon, though some reports on carbon storage in mangrove forests. Malaysia is highly committed to this matter through various international signatories and national level initiates such as through the establishment of the Malaysian Climate Action Council, Twelve Malaysian Plan, and National Policy on Biodiversity. Despite these, Malaysia still requires extensive data and research to realize the blue carbon potential. Strong coordination and cooperation between Federal/State, amendment to current law, and incorporation of GIS and Lidar technology in research. With these improvements, it is hoped that Malaysia can capitalize on the blue carbon potential and enhance its preservation and protection.